Superplasticity in Zn-based alloys - Naziri, Hurmuze (Cranfield University, 1972)
This thesis is concerned with two-basic zinc-based superplastic . alloys, the virtually. single-phase Zn --0.4 wt % Al alloy and the two-phase Zn - Al eutectoid alloy. -The first investigation is concerned with superplasticityin the Zn - 0.4 % wt Al alloy, while the second investigation is devoted to the effect-of copper additions on-the behaviour of the Zn. - Al eutectoid superplastic alloy and the possible mechanisms operating during deformation. A-zinc - 0.4 Al alloy was developed, which showed a. remarkable degree of superplasticity. at room. temperature, and. elongations of greater than 500% could be obtained at the relatively fast crosshead velocity of 0.1 inch/min. The strain7rate sensitivity (m) was found to increase with strain up to 300% on elongation (. 35 -*-. 5)-parallel to the rolling . direction. and it was also found to be anisotropic in-the plane of the sheet. The strain ratio r was also strain dependent and varied in the plane of the sheet. At 900 to the rolling direction, the strain ratio. increased from . 35 to . 75 after an elongation of 350%, that is, tending to unity (isotropy). Texture determination after straining showed a marked change and agreed qualitatively with the change in strain ratio. Grain growth occurred at room temperature, but was observed to be inhibited on superplastic deformation. Surface observations after deformation revealed that grainboundary sliding was taking place; fracture behaviour, though characteristically ductile in nature, varied with strain-rate. This alloy obeyed the Hall-Petch relationship above. a certain critical grain size, below which it was inapplicable, due to the occurrence of superplasticity. Thin-foil transmission-electron microscopy showed the importance of a dislocation recovery Mechanism in the interpretation. of this deformation behaviour, and calculations based on the current theories of volume and grainboundary diffusion, grainboundary sliding and dislocation climb/recovery, showed-that a grainboundary sliding/dislocation-climb recovery model could reasonably predict the observed. strain rate sensitivity and strain-rate. Biaxial tests confirmed the anisotropic properties observed in uniaxial. tests and also in punch-stretching the effect of-friction on cup height was contrary to that observed with workhardening metals. In the second investigation, measurements of. the-flow stress (af) and. strain-rate. sensitivity (m). over a wide range of strain- . rates (6)-and temperatures between -75-to 3000C have been made on a range of superplastic alloys, based on. the Zn - Al eutectoid, but with additions of up to 1% copper. These additions do not significantly affect af or m above about-1500C. The peak in the m. -ý curve is not displaced. by these-copper additions at temperatures above 1500C. Increasing the grain-size (L) increases af for. temperatures above about 600C but decreases. of-below this temperature.. With increasing-grain-size, the peak in m-value moves towards lower L, The dependence of af vs.. La showed that the exponent a. was strain-rate dependent and varied, from 0.6 to I at 2500C. The exponent b in the relation ý vs. 1 was independent F of stress and varied from 1.8 at 2500C to 3 at L 200C. The activation energy was grain-size and stress-dependent, and for the smallest grain size (. 55 jim), a value. of about 14 k. cal/mole was obtained in the superplastic region, while a value of near 20 k-cal/mole was obtained at the low 6 region. Creep-rate - measurements-at room-temperature showed that the secondary creep- rate decreased with increasing copper. content,, by a factor-of about 120 between 0 and 1.0% copper. . Increasing the grain size from 0.55 Um to 1.75 Um decreased the creep-rate further by a-factor varying from 10-50 times and thus an overall gain in creep resistance of 1200 times can be obtained. Uniaxial tension, torsion and_camplastometer tests were. used to cover strain-rates between. 10 3. to 104'. -mirCl in order experimentally to determine the multistage. af -e curve. Hot-totsion stress-strain curves were typical of those shown in previous published work on hot working, and showed that a steady-state stress was obtained during superplasticity. . In uniaxial tension, elongations of greater than 1000% were obtained at the very high initial strain-rate of 1.6 x 101 min-1. Grain coarsening occurred during deformation and was found to be strain-rate and strain dependent. Thin-foil transmission electron microscopy showed the extensive activity. of dislocations and diffusional processes. Dislocation-free structures and rounded interphase boundaries-were observed under . superplastic. conditions. Also, though many of the grains appeared equiaxed after deformation, a variety of odd-shaped grains were observed, particularly in hot torsion, where there was evidence of accelerated spherodization. Fracture. behaviour was dependent on grain size, temperature and strain-rate sensitivity. Calculated of curves,. from current theories, suggested that a dislocation-climb-recovery/grainboundary sliding model, based on grainboundary diffusivity was the operating mechanism during superplasticity.